THE HISTORY OF PEUSIJUEK IN ISLAMIC INTEGRITY - An-Nabawi, Muhammad Munir (Fakultas Ushuluddin Adab dan Dakwah IAIN Lhokseumawe, 2021)
Peusijek is one of the habits of the Aceh society that is still preserved and practiced. Peusijek as a culture that has been part of Islam, especially the Islam's society, this study wants to reveal how Peusijek is believed to be a religious community confidence is not entirely purely from the teachings of Islam. This research uses a qualitative approach with descriptive type Peusijek is believed by the Aceh community as one of the rituals associated with religion to religion, because peusijek is loaded with the valuable values and beliefs of Islamic values, so it becomes a trust.